2014
DOI: 10.5430/jnep.v4n9p163
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of electronic health record use in simulation

Abstract: Background/Objectives: Use of an electronic health record (EHR) system is a necessary part of the educational experience of nursing students. The purposes of this evaluation project were to ascertain from baccalaureate nursing students their perceptions of the importance of an EHR system and simulation to their education and their evaluations of one particular simulation/EHR system (S/EHR). Methods: Sixteen baccalaureate nursing students completed a survey, following use of the S/EHR in simulated clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…18,[27][28][29] To enhance students' nursing informatics competencies when students not only look up patients' information but also document assessment findings and nursing processes, AEMRs have been adopted as a more efficient way to obtain concrete, practical knowledge and skill. 2,13,15,33 Our findings demonstrated that participants regarded the AEMR writing function as the most important component of AEMRs, as students could actually document patients' data during their clinical practicum. Without this function, students felt that they were passive observers rather than active doers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…18,[27][28][29] To enhance students' nursing informatics competencies when students not only look up patients' information but also document assessment findings and nursing processes, AEMRs have been adopted as a more efficient way to obtain concrete, practical knowledge and skill. 2,13,15,33 Our findings demonstrated that participants regarded the AEMR writing function as the most important component of AEMRs, as students could actually document patients' data during their clinical practicum. Without this function, students felt that they were passive observers rather than active doers.…”
Section: Discussionmentioning
confidence: 89%
“…All suggested questions for the FGIs were based on a literature review of previous studies related to AEMRs. [12][13][14][15][16][17][18][19][20][21][22][27][28][29] Examples of the prompt questions that were used to guide the FGIs included the following: (1) how do EMRs facilitate or obstruct students' clinical practicum? (2) If AEMRs are to be developed, what are the functions to be included?…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers found that simulated EHRs help enhance students' skills in electronic documentation [24,41,42] and aid in the development of positive attitudes and perspectives about electronic records [43,44]. The integration of simulated EHRs also enhances students' confidence and self-efficacy in using electronic records [23,[44][45][46] and increases informatics knowledge and competency [16,40,47]. Despite these benefits, factors such as cost and faculty expertise continue to be major challenges in integrating simulated EHRs in nursing education [18,34,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Along with physicians, nurses, and other healthcare providers, pharmacists utilize electronic medical records (EMRs) for tasks such as medication reconciliation, computerized physician order entry (CPOE), eprescribing, and clinical decision support, but it is only recently that EMR training has been incorporated into pharmacy curricula [1]. Many healthcare disciplines, including nursing and medicine, are incorporating curricular content on EMR use and web-based patient centered modules to ensure trainees have adequate exposure to core medical content [2][3][4][5][6]. In the United States of America (USA), the Accreditation Council for Pharmacy Education (ACPE) recognizes professional communication and health informatics as two didactic content areas that are central to a contemporary, high-quality pharmacy education [7].…”
Section: Introductionmentioning
confidence: 99%